2018
DOI: 10.1002/cta.2574
|View full text |Cite
|
Sign up to set email alerts
|

Power maximization from resonant electromagnetic vibration harvesters feeding bridge rectifiers

Abstract: In this paper, it is shown that, for resonant electromagnetic vibration energy harvesters (REVEH) feeding diode bridge rectifiers, it is possible to quantify how close the ideal load condition is to the actual load condition. For this purpose, a new figure of merit, the REVEH exploitation factor (REF), is introduced. The higher the REF, the higher the REVEH exploitation. Moreover, by using the REF, a suitable technique for increasing the extracted power in a frequency region of interest is investigated. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The feasibility of piezoelectric energy harvesting (PEH), already successfully demonstrated in many exciting application scenarios, 33–37 allows the conversion of mechanical movements into electricity. However, the application requirement typically mandates the PEH systems to operate in nonresonance conditions, leading to significant energy extraction degradation due to its inherent capacitance ( C p ).…”
Section: Energy Harvesting Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of piezoelectric energy harvesting (PEH), already successfully demonstrated in many exciting application scenarios, 33–37 allows the conversion of mechanical movements into electricity. However, the application requirement typically mandates the PEH systems to operate in nonresonance conditions, leading to significant energy extraction degradation due to its inherent capacitance ( C p ).…”
Section: Energy Harvesting Interfacesmentioning
confidence: 99%
“…| ENERGY HARVESTING INTERFACESWith the emergence of IoE, the limited battery capacity for supporting various wearable and implantable devices is becoming a major bottleneck. Energy harvesting, which can theoretically achieve full system autonomy and even battery-less operation, is becoming an attractive system-level alternative.4.1 | Capacitive PEH interfaceThe feasibility of piezoelectric energy harvesting (PEH), already successfully demonstrated in many exciting application scenarios,[33][34][35][36][37] allows the conversion of mechanical movements into electricity. However, the application requirement typically mandates the PEH systems to operate in nonresonance conditions, leading to significant energy extraction degradation due to its inherent capacitance (C p ).…”
mentioning
confidence: 99%
“…Therefore, a second objective to fulfill is the matching of the RVEH with its optimal load impedance, frequency by frequency. This is the aim of the so-called electrical tuning techniques (ETTs) [96][97][98][99][100][101][102]. It is worth noting that the application of the ETTs of course does not change the mechanical resonance frequency of a RVEH.…”
Section: Definition Of Tuning Techniquesmentioning
confidence: 99%
“…Step-down piezoelectric transformers have been widely studied, and they have been developed with various circuit topologies and control techniques [8], [9], [10]. Most studies have concluded that DC transformers, including piezoelectric-based transformers, need to have a simple cir-cuit structure to take full advantage of their small size, and they should be operated at a frequency with the maximum gain under the maximum load condition to improve efficiency [11], [12].…”
Section: Introductionmentioning
confidence: 99%